2020
DOI: 10.3390/ijerph17186483
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enteric Viruses and Bacterial Indicators in a Sewage Treatment Center and Shallow Water Bay

Abstract: The incidence of enteric viruses in treated wastewater and their potential release into the environment or use for agriculture are very critical matters in public health. In our study, PCR (polymerase chain reaction) analysis of enteric viruses was performed on 59 samples of influents and effluents collected from Tubli wastewater treatment plant (Water Pollution Control Center (WPCC)) and Tubli Bay, where the effluents were discharged, in Kingdom of Bahrain during two sampling periods. Four clinically essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…In addition, our study showed the presence of EVs not only in raw but also in treated wastewater (in almost 30% of these samples). Other studies also documented higher detection rate of EVs from both raw and treated wastewater [ 47 , 48 ],…”
Section: Discussionmentioning
confidence: 87%
“…In addition, our study showed the presence of EVs not only in raw but also in treated wastewater (in almost 30% of these samples). Other studies also documented higher detection rate of EVs from both raw and treated wastewater [ 47 , 48 ],…”
Section: Discussionmentioning
confidence: 87%
“…As the largest biological sink, sewage contains a pool of infectious agents as well as other organic and non-organic materials. A wide variety of infectious agents, including bacteria, fungi, parasites, and viruses can be found in sewage, which makes it an important transmission vehicle (2). Enteric viruses, including some members of rotaviruses, enteroviruses, astroviruses, noroviruses, adenoviruses, hepatitis A virus (HAV), and hepatitis E virus, are transmitted mainly through the fecal-oral route (3).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is a lot of undetected community carriage and transmission of ESBL-PE at the human-animal-environment interface [15] even though there is inadequate local evidence for this. Such insufficient evidence may not competently inform prevention and control strategies including policies to govern management of AMR in the LMICs [16,17].…”
Section: Introductionmentioning
confidence: 99%